Reduction EMI of BLDC Motor Drive Based on Software Analysis - Navid Mousavi; Tohid Rahimi; Homayoun Meshgin Kelk (Advances in Materials Science and Engineering)
In the BLDC motor-drive system, the leakage current from a motor to a ground network and existence of high-frequency components of the DC link current are the most important factors that cause conducting interference. The leakage currents of the motors, flow through common ground, will interfere with other equipment because of the high density of electrical and electronic systems in the spacecraft and aircrafts. Moreover, generally there are common DC buses in the mentioned systems, which aggravate the problem. Function of the electric motor causes appearance of the high-frequency components in the DC link current, which can interfere with other subsystems. In this paper, the analysis of electromagnetic noise and presentation of the proposed method based on the frequency spectrum of the DC link current and the leakage current from the motor to the ground network are done. The proposed method presents a new process based on the filtering method to overcome EMI. To cover the requirement analysis, the Maxwell software is used.